Exercise-Induced Changes in Tumor Growth via Tumor Immunity - Spiliopoulou, Polyxeni (Sports (Basel), 2021)
Immunity in the tumor microenvironment plays a central role in tumor development. Cytotoxic immune cells act against tumors, while tumors manage to trigger immunosuppressive mechanisms for defense. One bout of physical exercise acutely regulates the immune system inducing short-term redistribution of immune cells among body organs. Repeated acute immune cell mobilization with continuing exercise training results in long-term adaptations. These long-term exercise-induced changes in the immune system arise both in healthy and in diseased populations, including cancer patients. Recent preclinical studies indicate that physical exercise may have a positive impact on intra-tumoral immune cell processes, resulting in tumor suppression. This short narrative review describes the effect of physical exercise on tumor growth as detected via changes in tumor immunity. Research evidence shows that exercise may improve tumor-suppressive functions and may reduce tumor-progressive responses and mechanisms of immune cells, controlling tumor development. Specifically, it seems that exercise in rodents triggers shifts in tumor infiltration of macrophages, neutrophils, natural killer cells, cytotoxic and regulatory T lymphocytes, resulting in tumor suppression. These recent promising data suggest that physical exercise could be combined with anticancer immunotherapies, although exercise parameters like intensity, duration, and frequency need to be evaluated in more detail. More research is needed to investigate the effect of exercise in other immune cell subtypes and their possible connection with tumor growth, whilst information from human tumors is also required.